If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + 1) + 2k = 13 Reorder the terms: 3(1 + k) + 2k = 13 (1 * 3 + k * 3) + 2k = 13 (3 + 3k) + 2k = 13 Combine like terms: 3k + 2k = 5k 3 + 5k = 13 Solving 3 + 5k = 13 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5k = 13 + -3 Combine like terms: 3 + -3 = 0 0 + 5k = 13 + -3 5k = 13 + -3 Combine like terms: 13 + -3 = 10 5k = 10 Divide each side by '5'. k = 2 Simplifying k = 2
| 2x^4=120 | | -7x^2-24x-9=0 | | 3m+4=12 | | p14=-20 | | m+80=140 | | t(25)=0.07(25)^3/2 | | 6x=-18y-12 | | 5x-3=6x-2x | | 0y-5(1+y)=3(2y-2)-20 | | F(x)=(t-1)(t+3) | | 2t-7-52=11 | | 3x-5=7x-49 | | 42=-6g | | 4/9y-3 | | e^5x+8=13 | | -3(1+4.5r)=-17.5 | | 1x^2+4x-6=0 | | v/7=-13 | | 7.4r+9-2r=25.2 | | 7x+7=3-5z | | m=4m+11 | | X+(-56)=-7 | | -12=12m | | 0.25(20)+0.7x=0.6(20+x) | | 5x-4-x=2x-1 | | 7/8y-3 | | 2x+5=-40+7x | | -8h=-56 | | A-(-9)/-2=11 | | 3x+5(-1+x)=-21 | | 8y-8=8y+4 | | 2y-3=2y+y |